Fatores de risco cardiovascular e práticas de cuidado entre mulheres: um estudo misto - Oliveira, Gabriela (2019)
Cardiovascular diseases (CVD) are one of the major causes of deaths and hospitalizations, with risk factors being one of the main implications for development. Women, who are predisposed to factors, hormonal conditions, habits and sometimes do not prioritize health care, stand out. From the research questions: What is the sociodemographic, health profile and cardiovascular risk factors among the women attended in the Primary Health Care of Santa Maria? What are the knowledge and care practices of these women about risk factors for cardiovascular disease? The objective of this study was to investigate the risk factors for cardiovascular diseases and to understand the knowledge and care practices of women treated at Primary Health Care in Santa Maria. A mixed study was developed, which had as its scenario the urban services of Primary Attention to Health and, in the qualitative stage, the Family Health Units were delimited. The quantitative stage was performed through a semistructured interview that used an instrument to characterize the population and identification of cardiovascular risk factors, in addition to the Framingham Scale, 289 women participated in this phase, the descriptive analysis was performed in software R version 3.4.3. The qualitative stage was based on the participatory research, with the production of the data through semi-structured interview, associated to a technique of creativity and sensitivity and the development of narratives, which made possible the data analysis and the construction of the argumentative nuclei, participated in this stage 30 women. Ethical precepts involving human research were followed. In the quantitative stage, there was a predominance of white participants (n = 187; 64,7%), catholic (n = 141; 48,8%), married (n = 98; 34,0%), salaried or autonomous (n = 128; 44,6%), who studied in a period of zero to eight years (n = 134; 46,4%), and received from one to two salaries (n = 91; 31,5%). The main factors identified were sedentarism (n = 176; 60,9%), contraceptive use in women of childbearing age (n = 178; 58,9%), stress (n = 175; 60,6%), depression (n = 116; 40,1%), obesity (n = 112; 38,8%), systemic arterial hypertension (n = 97; 33,6%), consumption of alcoholic beverages (n = 86; 29,8%), history of cardiovascular events in the family (n = 75; 26,0%) and dyslipidemia (n = 74; 25,6%). The majority of the participants were classified as high risk according to Risk 1 (n = 81; 57,4%) and low according to Risk 3 (n = 74, 92.5%). At the qualitative stage, the users demonstrated knowledge about the main risk factors and CVD, which came from several sources. Regarding the care practices, some of the participations were focused on safety measures, food, recreational actions and medicines ingested, yet others not achievable, with the same recognition of health problems. The professionals were considered important in the prevention and control of the risk factors and the CVD, the users listed strategies to strengthen the performance, and some pointed weaknesses in the assistance provided. It is concluded that important risk factors were identified, mainly the modifiable ones, related to the habits and the behavior of the women. The participants had knowledge about the risk factors and presented divergence in the practice of care practices, demonstrating the importance of actions focused on the needs and singularities of the population.